Foucault’s Dismissal of Ideology: A Critique - Prasai, Khagendra (Journal of Political Science, 2021)
Foucault dismisses ideology as an object of investigation in understanding power relations for three important reasons bearing on his rejection of true-false distinction, dismissal of reference to subject and trivialization of ideology. This paper argues against Foucault's claim and shows that investigation of ideology constitutes an important task in understanding relation of domination—which is substantiated by demonstrating firstly that the true-false distinction is not only ontologically real but also morally warranted; and secondly that ideology is not merely a passive effect of infrastructure of an oppressive social system but is in reciprocal relation with it and therefore plays an indispensably important role in maintaining the system in general and the present-day capitalism in particular.